Treatment and monitoring of a high-density population of bare-nosed wombats for sarcoptic mange - Tanya N. Leary; Lyn Kaye; Olivia Chin; Kar Yee Phoon; David Phalen (PLoS ONE, 2025)
Sarcoptes scabiei causes a fatal disease (mange) in bare-nosed wombats (BNWs) (Vombatus ursinus) across their range and can threaten isolated populations with extinction. Repeated dosing of moxidectin (Cydectin®) at a dosage rate of 0.5 mg/kg is effective at treating individual BNWs but is difficult to administer on a population basis where treatment success has varied. This paper documents the temporary (~20 month) eradication of mange from a semi-isolated population of BNWs using repeated dosing of Cydectin® administered by burrow flaps. Treated BNWs were marked with nontoxic paint and selected burrows were monitored with camera traps demonstrating that 64–96% of wombats in the population were treated with each dosage. Treatment success was attributed to the installation of burrow flaps on all burrows in the treated area. This treatment program shows that isolated high-density populations can be successfully treated for S. scabiei infection with repeated dosages of Cydectin® (0.5 mg/kg) and questions the need for higher dosages that have been advocated. Mange returned to the population of BNWs after 20 months possibly as the result of migration of an infected BNW from a nearby population, suggesting mange affected populations may require periodic retreatment. Monitoring of burrow entrances confirmed that burrows provide habitat used by many species of birds, reptiles, and mammals, and suggest burrows could be occasional sites of mange spillover among species. Camera trap monitoring also showed when BNWs in this population leave and return to their burrows; how many BNWs enter a burrow and explore the burrow entrances each night; and how these parameters are impacted by season and mange status; variables that are valuable to know when treating populations of BNW for mange.